Diderichsens Modell als oberflächliches Linearisierungsapparat für X-bar Grammatiken - Radoev , Konstantin (Zeitschrift „Germanistik und Skandinavistik“ / Journal for German and Scandinavian Studies, 2024)
The article presents a theoretical comparison between the descriptive force of two models of the Mainland Scandinavian sentence (focusing in particular on Swedish and Danish) – the traditional functional model by Paul Diderichsen, split into a front, center, and final field, and the tripartite generative X-бар model, split into a complementiser phrase (CP or CvP for the purposes of the article, also called the contextual phrase f. p. a.), an inflectional phrase (IP or IvP f. p. a.), and a verb phrase (vP or LvP f. p. a.). The text will focus on the left periphery. Based on previous research, the article puts forward the hypothesis that such a comparison could serve as the starting point for the construction of a surface-level linear model of the Bulgarian sentence, similar to the Diderichsen model. Such a model can have potential application as a tertium comparationis in the teaching of Mainland Scandinavian languages to students with L1 Bulgarian, and for foreigners learning Bulgarian as an L2.